(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The present study was conducted to confirm the effects and correlations of estradiol hormone on some major clotting factors (fibrinogen FI , prothrombin FII, stable factor F VII, antihemophilic factor FVIII, and chrismas factor IX) during pregnancy phases. Seventy five (75) pregnant women at different stages of pregnancy and were sub- divided into third groups according to period of gestational phases , included twenty five (25) pregnant women in each group (first, second, third trimesters). Twenty (20) volunteer non-pregnant non-lactating women were involved in this study and used as a control group. All ages of tested women ( pregnant and non- pregnant) were between 25 year to 35 year old . Regarding levels of estradiol hormone , they were showed insignificant elevation (p>0.05) during first trimester and remarkable increase (p< 0.05) during second and third trimesters when matched with their counterparts of non- pregnant group. About concentrations of fibrinogen factor (FI) , they were indicated a significant heightening (p< 0.05) during all phases of pregnancy in matching with control group, and these concentrations have a positive correlation (r =0.714) with levels of estradiol. Activities of prothrombin factor ( F II) were significantly elevated (p<0.05) throughout pregnancy phases than of non- pregnant women , and have a significant positive correlation ( r =0. 532) with estradiol hormone . Levels of stable factor (F VII ) activity indicated insignificant increase (p> 0.05 ) in first and second trimesters and its activities become increased (p< 0.05) at third trimester in a comparison with those of control group, and pointed out a significant positive correlation ( r = 0.412 ) with estradiol level . Estimation of intrinsic pathway activities (antihemophlic factor FVIII and Chrismas factor FIX ) were showed a progressive elevation (p< 0.05) during first, second, and third trimesters in a comparison with control group, and these activities confirmed a significant positive correlation (r =0.260 , r =0.632, respectively) with estradiol.